2011
DOI: 10.1039/c0ob00627k
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of (−)-20-epiuleinevia stereocontrolled one-pot asymmetric azaelectrocyclization followed by novel 1,4-addition reaction

Abstract: The first asymmetric total synthesis of an indole alkaloid, (-)-20-epiuleine, containing the 2,3,4-trisubstituted piperidine core, was achieved using a stereocontrolled one-pot asymmetric 6π-azaelectrocyclization followed by a stereoselective 1,4-addition reaction of the unsaturated ester with a Grignard reagent resulting from the novel neighboring participation of the hydroxyl group in cis-aminoindanol as a chiral nitrogen source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…For example, 292 was transformed into (-)-hippodamine after a series of reactions. Similar strategies were applied in the stereocontrolled synthesis of (-)-dendroprimine, (+)-7-epidendroprimine, (+)-5-epidendroprimine, (+)-5,7-epidendroprimine, 65 (-)-20-epiuleinevia, 66 and (-)-dendroprimine. 67 Scheme 52…”
Section: Review Syn Thesismentioning
confidence: 99%
“…For example, 292 was transformed into (-)-hippodamine after a series of reactions. Similar strategies were applied in the stereocontrolled synthesis of (-)-dendroprimine, (+)-7-epidendroprimine, (+)-5-epidendroprimine, (+)-5,7-epidendroprimine, 65 (-)-20-epiuleinevia, 66 and (-)-dendroprimine. 67 Scheme 52…”
Section: Review Syn Thesismentioning
confidence: 99%
“…This powerful methodology was applied to the total synthesis of three natural indole alkaloids, such as (-)-dendroprimine, 211 (-)-corynantheidine, 212 and (-)-20-epiuleine, 213 Diastereoselective nickel-catalysed asymmetric four-component domino Reformatsky reactions have been developed by Dondoni et al with the aim of achieving chiral C-glycosyl b-amino esters. 138 As shown in Scheme 1.125, an in situ initial coupling of chiral C-glycosyl aldehydes with p-methoxybenzylamine gave the corresponding imines.…”
Section: Multicomponent Reactions Based On the Petasis Reactionmentioning
confidence: 99%
“…Several well‐designed pluripotent molecular platforms have been developed by different research groups . Katsumura and Vanderwal's groups have extensively studied substituted dienals possessing well‐defined and dense array of interrelated functionalities . Katsumura and co‐workers found that the introduction of an ester group at the C 3 ‐position of dienals dramatically altered the course of the reaction due to the remarkable accelerating effect of this substituent.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, dienals underwent pericyclic rearrangement in refluxing toluene solution via [1,5]‐H shift of the aldehyde hydrogen to afford the intermediary vinyl ketene intermediate which was subsequently captured by an alcohol, olefin, or imine to afford esters, cyclobutanones, or azacyclobutanones (Scheme ) . They also succeeded in accelerating the key 6π‐aza‐electrocyclization step for the synthesis of multisubstituted piperidine and pyridine derivatives from 1‐azatrienes . The substituent effect was rationalized based on molecular orbital calculation which supports the contention that the substituent at the C 3 ‐position of dienal reduces the activation energy of the process …”
Section: Introductionmentioning
confidence: 99%